A new labdane-type diterpenoid from Leonurus japonicus. Issue 7 (3rd July 2019) - Jiang, Min-Hong; Hu, Yue; Jiao, Lin; Dong, Pan; Yin, Sheng; Zhao, Zhi-Min; Yang, De-Po; Wang, Dong-Mei
Abstract: Five fractions prepared from the crude extract of Leonurus japonicus were examined in order to determine their cytotoxic potential. Under the bioassay guidance, a new labdane-type diterpenoid (1 ), and nine known ones (2–10 ) along with a seco -labdane (11 ) were isolated from the aerial parts of Leonurus japonicus . The structure elucidation was primarily based on comprehensive spectroscopic analyses, including HRESIMS, IR, and 1D and 2D NMR methods. Compound4 (6β-hydroxy-15, 16-epoxylabda-8, 13(16), 14-trien-7-one) exhibited potential cytotoxicity against HeLa cell line (IC50 = 23.75 μM). Abstract :